THE EFFECT OF CARBONATED, ISOTONIC AND YOGHURT DRINKS IMMERSION ON THE ROUGHNESS OF BULK-FILL COMPOSITE RESIN - Ayu Khoirun Nisa; Diah Ajeng Purbaningrum; Lusiana Batubara; Faizah Fulyani (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Composite resins are dental restorative materials that are widely used and have high aesthetic value compared to other materials. However, acidic environmental conditions can degrade the composite resins, resulting in increased surface roughness of the resin, and consequently lead to an increased risk of caries.Objective: the purpose of this study was to evaluate the effect of immersion in acidic drinks on the surface roughness of composite resins,Method: In this study 24 samples of bulk fillTM composite resins were used. Samples were divided into four groups. Each sample was immersed for 5 seconds in either artificial saliva (control), carbonated beverage, isotonic, or yogurt, and followed by 5 seconds immersion in saliva. This cycle was repeated for 20 times for 14 consecutive days. The roughness of composite resin before and after 14 days immersion was measured by using a profilometer. Microscopic structures were analyzed by Scanning electron Microscope (SEM). Statistical analysis was used paired t-test, Anova and Post Hoc LSD.Results: Data from each sample group was normally distributed- with p > 0.05. The paired t-test for each group showed a p-value < 0.05, which indicates there was a significant difference between surface roughness before and after immersion. ANOVA analysis revealed that there was a difference in the surface roughness between groups LSD test, showed that there was difference in the surface roughness between artificial saliva with carbonated drink, isotonic drink with carbonated drink, yoghurt drink with carbonated drink (p<0.0001), between artificial saliva group with yoghurt drink, yoghurt drink with carbonated drink, yoghurt drink with isotonic drink (p <0.05) which means there was a significant difference between group. Meanwhile, the isotonic drinks with artificial saliva obtained results (p>0.05), which means there is no significant difference.Conclusion: Exposure of carbonated drinks, yoghurt drinks, and isotonic drinks can significantly increase the roughness of the surface Bulk Fill resin composite compared to exposure of artificial saliva.Keywords: Composite resin, Bulk Fill, Surface Roughness, Acid